2008
DOI: 10.1007/s10601-007-9038-4
|View full text |Cite
|
Sign up to set email alerts
|

A Global Chance-Constraint for Stochastic Inventory Systems Under Service Level Constraints

Abstract: We consider a class of production/inventory control problems that has a single product and a single stocking location, for which a stochastic demand with a known non-stationary probability distribution is given. Under the widely-known replenishment cycle policy the problem of computing policy parameters under service level constraints has been modeled using various techniques. Tarim and Kingsman introduced a modeling strategy that constitutes the state-of-the-art approach for solving this problem. In this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 26 publications
(80 reference statements)
0
35
0
1
Order By: Relevance
“…We performed tests using four different ordering cost values a ∈ {40, 80, 160, 320} and two different σ t /d t ∈ {1/3, 1/6}. The planning horizon length takes even values in the range [24,50] when the ordering cost is 40 or 80 and [14,24] when the ordering cost is 160 or 320. The holding cost used in these tests is h = 1 per unit per period.…”
Section: More Extensive Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed tests using four different ordering cost values a ∈ {40, 80, 160, 320} and two different σ t /d t ∈ {1/3, 1/6}. The planning horizon length takes even values in the range [24,50] when the ordering cost is 40 or 80 and [14,24] when the ordering cost is 160 or 320. The holding cost used in these tests is h = 1 per unit per period.…”
Section: More Extensive Testsmentioning
confidence: 99%
“…Empirical results showed that such a model is unable to solve large instances, but Tarim and Smith [23] introduced a more compact and efficient Constraint Programming (CP) formulation of the same problem that showed a significant computational improvement over the MIP formulation. A stochastic constraint programming [22] approach for computing (R n , S n ) policy parameters is proposed in [14]. In this work the authors drop the mild assumptions originally introduced by Tarim and Kingsman and compute optimal (R n , S n ) policy parameters.…”
Section: Introductionmentioning
confidence: 99%
“…, Zipkin(1989), Lovejoy(1990), Morton and Pentico(1995), Iida(2002), Tarim and Kingsman (2004), Levi et al(2007), Rossi et al(2008), Guan and Liu(2010) 두 번째 분류의 연구들은 비정상 수요에서 구매자 관점의 재고관리 정책에 관한 연구이다. Sethi and Cheng(1997) (1)   기 수요를 예측한다.…”
Section: 서 론unclassified
“…More recently, scenario-based stochastic constraint programming [25], and cost-based filtering for stochastic constraint programming [24,26] have been proposed. Lastly, the concept of global chance constraints that was introduced by Rossi et al [23] is of particular interest to our work.…”
Section: Introductionmentioning
confidence: 99%